2014
DOI: 10.3109/02699052.2014.916417
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life of patients with Parkinson’s disease

Abstract: The QoL of patients with PD is influenced by many interacting factors related to their health, personal relations, care, communication and society. To improve the QoL and care for persons with PD, all factors should be taken into account. Person-centred care recognizes the uniqueness and capabilities of patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…3.3 | Narrative analysis of papers by social role category 3.3.1 | General social functioning General social functioning included papers (n = 16) that described overall socialization or social functioning but did not discuss a specific social role. [21][22][23] Papers also described treatments and interventions to improve Parkinson's symptoms including "typical" PD treatments (ie, medication and deep brain stimulation [DBS] surgery), exercise interventions (eg, tango class), and educational programs (eg, psychoeducation). Gunnery et al described that facial masking was associated with social functioning problems such as social rejection, although this finding was attenuated after controlling for depression.…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…3.3 | Narrative analysis of papers by social role category 3.3.1 | General social functioning General social functioning included papers (n = 16) that described overall socialization or social functioning but did not discuss a specific social role. [21][22][23] Papers also described treatments and interventions to improve Parkinson's symptoms including "typical" PD treatments (ie, medication and deep brain stimulation [DBS] surgery), exercise interventions (eg, tango class), and educational programs (eg, psychoeducation). Gunnery et al described that facial masking was associated with social functioning problems such as social rejection, although this finding was attenuated after controlling for depression.…”
Section: Key Pointsmentioning
confidence: 99%
“…40 Receiving support from their family helped make people living with Parkinson's feel more secure and motivated to maintain their treatment regimen. 23,42,58 Additionally, for some people living with Parkinson's who were unable to work, parenting or family relationships became a higher priority. Eleanor Singer compared people living with Parkinson's to age-matched controls and found no difference in parental role satisfaction.…”
Section: Family Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Factors found to affect communication, and consequently quality of life, are impairment of speech function (e.g., vocal loudness) and also changes in cognition (e.g., reduced verbal fluency and memory problems) [8]. In a systematic review, Barnish et al [9] found a positive correlation between greater cognitive impairment and more pronounced communication difficulties in 9 of 10 studies.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative study [30] reported motor signs as a significant predictor of communication in the PDQ-39. In addition, much qualitative research [3133] has vividly described how patients with PD perceived their movement and communication difficulties to be distressing and socially embarrassing. Such stigmatized feelings might subsequently lead to decreased social interaction.…”
Section: Discussionmentioning
confidence: 99%